Inhibition of placental P-glycoprotein: impact on indinavir transfer to the foetus - Sudhakaran, Sreeja (Blackwell Science Inc, 2008)
AIMS: To investigate the effect of P-gp inhibition on the maternal to foetal transfer of indinavir. METHODS: Term human placentae (n = 12) were from non-HIV infected women. Maternal to foetal transfer of indinavir was examined in the absence and presence of P-gp inhibitors PSC833 (n = 7) or ritonavir (n = 5), in the perfused human placenta. Antipyrine and [(3)H]-vinblastine were included as markers of passive diffusion and P-gp transport, respectively. These markers and indinavir were added to maternal perfusate at 0 min; PSC833 or ritonavir was added at 25 min. Steady-state maternal to foetal transfer clearance was calculated during control and inhibitor phases. Indinavir and vinblastine clearances were normalized to antipyrine clearance (clearance index). RESULTS: Indinavir clearance index increased between the control (0.25 ± 0.03) and PSC833 phases (0.37 ± 0.14) (95% CI of the difference −0.23, −0.002). Vinblastine clearance index increased from (0.25 ± 0.08) to (0.34 ± 0.06) in the control and PSC833 phases, respectively (95% CI of difference −0.14, −0.05). Indinavir clearance index was unchanged between control (0.34 ± 0.14) and ritonavir phases (0.39 ± 0.13) (95% CI of the difference −0.19, 0.08). Vinblastine clearance index increased from (0.24 ± 0.12) to (0.32 ± 0.12) in the control and ritonavir phases, respectively (95% CI of the difference −0.15, −0.009). CONCLUSIONS: Maternal to foetal transfer clearance of indinavir and vinblastine increased following P-gp inhibition. The potential role for co-administration of P-gp inhibitors with PIs to reduce perinatal HIV transmission warrants further investigation.